SOSIALISASI PENERAPAN AKUNTANSI RUMAH TANGGA PADA IBU-IBU PKK DI DESA SIMO KECAMATAN KENDAL KABUPATEN NGAWI - Yuwita Ariessa Pravasanti; Iin Emy Prastiwi; Dinda Maulid Rahmawati; Azizah Putri Az-Zahra; Nila Ayu Rusmala Dewi (LPPM ITB AAS Indonesia Surakarta, 2023)
Implementation of good financial management in the family realm is crucial to a happy family. Inappropriate financial management will bring families to various economic problems that lead to complex problems in the family. Household accounting and finance training is an alternative to being able to direct families so they can manage their finances wisely in order to create a happy family. The socialization method involves discussing accounting, applying household financial management to PKK mothers who are generally chosen because they are the spearhead of family financial planning in the Simo Village environment. As for the activities in the form of socialization of the introduction of accounting, the concept of financial management. Thus, socialization of household financial management is an alternative for housewives in Simo Village, Kendal District to be able to manage family finances more wisely and usefully.